A large anisotropic plasticity of l‐leucinium hydrogen maleate preserved at cryogenic temperatures. Issue 2 (13th March 2019) - Arkhipov, S. G.; Losev, E. A.; Nguyen, T. T.; Rychkov, D. A.; Boldyreva, E. V.
Abstract : Unusually large plasticity of an organic crystal at liquid nitrogen temperature is described and rationalized using variable‐temperature single‐crystal X‐ray diffraction data. Abstract : l ‐Leucinium hydrogen maleate crystals are very plastic at ambient conditions. Here it is shown that this plasticity is preserved at least down to 77 K. The structural changes in the temperature range 293–100 K were followed in order to rationalize the large anisotropic plasticity in this compound. To the best of our knowledge, this is the first reported example of an organic compound remaining so plastic at cryogenic conditions.